“Among the Word Animals”:: A Conversation with Marilyn Dumont - Andrews, Jennifer (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
Marilyn Dumont discusses the influence of her Cree and Métis ancestry on her poetry, with particular emphasis on the women who raised her. Stereotypical notions of the role of the Aboriginal writer, and misconceptions about the nature of oral tradition have both had their effects on the reception of Dumont 's writing. Personal disclosure in poetry can have an important normalizing effect, alleviating the shame that often accompanies close observation of one's psyche and family. Dumont has developed a flexible sense of writing as ritual, quite apart from the communal rituals of Catholicism and Aboriginal belief with which she grew up.